Building a strategic framework for quality improvement: a review of related research, management processes and lean methodologies - Shahzad Afzal Kayani; Ansar Abbas; Dian Ekowati (Cogent Education)
The constant evolution of healthcare and organizational structures demands a robust framework that caters to the requirements of individuals, teams and systems. This study develops a conceptual framework for quality improvement (QI) through a systematic review of research on informing QI research (InQuIRe), quality management processes (QMP) and lean principles. A systematic literature review (SLR), incorporating studies from Scopus, Web of Science (WoS) and CrossRef, was conducted to identify trends and inform the conceptual development of QI frameworks to identify studies published in English from October 2006 to September 2024. Integrating InQuIRe, QMP and lean management offers a theoretical basis for enhancing quality systems, promoting individual engagement and fostering effective team collaboration. Lean management supports a pull-based production model that aligns output with actual customer demand, thereby minimizing waste and enhancing responsiveness. The application of lean management principles across sectors, including education, can improve stakeholder engagement by fostering collaboration, minimizing resource waste and enhancing operational effectiveness. Ongoing enhancement encourages teams to improve performance and customer satisfaction. Organizations that adopt Lean methodologies emphasizing systems thinking and sustainable practices achieve better quality management (QM) outcomes.